Pain Management and Telemedicine: A Look at the COVID Experience and Beyond - Jamal Hasoon; Ivan Urits; Omar Viswanath; Alan D. Kaye (Health Psychology Research)
COVID-19 caused a drastic change in clinical medicine around the globe. In the United States, telemedicine was rapidly adopted on a wide scale to minimize direct patient interaction and to reduce the spread of the COVID-19 virus. Telemedicine also went hand in hand with the rapid movement of working remotely. This has provided several challenges to chronic pain management clinics along with other subspecialties. Telemedicine has also opened opportunities for providing valuable care for patients with significant barriers to healthcare professionals. Given the benefits and downfalls of telemedicine, it is ultimately up to the provider who has an established patient-physician relationship and best understands the patient's limitations and healthcare needs who can best determine which patient population telemedicine is appropriate for and how frequently it can be utilized for each individual patient.